Ethics-Aware Control Systems for Cyber-Physical Infrastructure (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
Cyber-physical infrastructure (CPI) systems -- power grids, water treatment networks, transport control systems, and telecommunications backbone -- integrate computational control with physical processes that have direct and irreversible consequences for human welfare, safety, and equity. Ethics-aware control systems embed ethical constraints -- safety prioritisation, equity in service distribution, democratic accountability, and environmental impact limits -- directly into the control algorithms that govern critical infrastructure behaviour. This paper proposes the Ethics-Aware CPI Control Framework (EACCF), a systematic design and evaluation of four ethics-aware control architectures -- constraint satisfaction control (CSC), multi-objective ethical optimisation (MOEO), participatory adaptive control (PAC), and safety-ethics co-design (SECD) -- applied to three CPI domains: smart power grid management, water distribution optimisation, and urban traffic control. EACCF introduces the Ethics-Aware Control Quality Score (EACQS) integrating safety constraint satisfaction, equity in resource distribution, democratic accountability, and operational efficiency. Key results: safety-ethics co-design achieves the highest EACQS (0.892); equity in resource distribution is the most challenging ethical constraint to satisfy simultaneously with operational efficiency; CSC achieves the highest safety constraint satisfaction (0.960). The framework provides ethics-aware control system design guidance for critical infrastructure operators and regulators.